Rangkaian Sosial dan Alternasi Kode dalam Komunitas Bugis Diaspora di Papua - Sukardi Gau (Balai Bahasa Provinsi Papua, 2019)
The simple writing still speak about two main issues, there are social series and code alternation. Both of issue above based on language circumstances in Bugis diaspora's community at Jayapura, Papua Province. In this context, social series are researched by consider pattern and social relationship structure Bugi's person and language perpuse in their social structure. Here after, commnication affair and social interaction in Bugis Papua's community is interposed to show code alternation form in communities social relationship most conceive of one important sociolinguistic issue. Besides, less of this study about Bugi's comer at Papua also as judgement to lift this topic.